Opportunities and Challenges of Artificial Intelligence in Digital Forensics - Syifaurachman Syifaurachman (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
Digital forensics research remains constrained, while the rapidly evolving digital landscape renders traditional forensic methodologies increasingly inadequate for modern investigative challenges. This work conducts a systematic literature review and bibliometric analysis of computer forensics, specifically targeting digital forensics applications. The study employed a systematic literature evaluation of the Scopus database using